A rapid method for isolation of bacterial extracellular vesicles from culture media using epsilon-poly-L–lysine that enables immunological function research - Wei, Shujin; Jiao, Dian; Xing, Wanli (Frontiers in Immunology, 2022)
Both Gram-negative and Gram-positive bacteria can release vesicle-like structures referred to as bacterial extracellular vesicles (BEVs), which contain various bioactive compounds. BEVs play important roles in the microbial community interactions and host-microbe interactions. Markedly, BEVs can be delivered to host cells, thus modulating the development and function of the innate immune system. To clarify the compositions and biological functions of BEVs, we need to collect these vesicles with high purity and bioactivity. Here we propose an isolation strategy based on a broad-spectrum antimicrobial epsilon-poly-L-lysine (ε-PL) to precipitate BEVs at a relatively low centrifugal speed (10,000 × g). Compared to the standard ultracentrifugation strategy, our method can enrich BEVs from large volumes of media inexpensively and rapidly. The precipitated BEVs can be recovered by adjusting the pH and ionic strength of the media, followed by an ultrafiltration step to remove ε-PL and achieve buffer exchange. The morphology, size, and protein composition of the ε-PL-precipitated BEVs are comparable to those purified by ultracentrifugation. Moreover, ε-PL-precipitated BEVs retained the biological activity as observed by confocal microscopy studies. And THP-1 cells stimulated with these BEVs undergo marked reprogramming of their transcriptome. KEGG analysis of the differentially expressed genes showed that the signal pathways of cellular inflammatory response were significantly activated. Taken together, we provide a new method to rapidly enrich BEVs with high purity and bioactivity, which has the potential to be applied to BEVs-related immune response studies.